Implementation of Education Management on Leading Class Program - Candra Wijaya; Budi Budi; Zulkhairi Zulkhairi; Mulkan Hasibuan; Edy Rosadi (STAI Hubbulwathan Duri, 2021)
This study aims to determine the planning, organization, implementation, monitoring, and evaluation of superior class education programs at MTsN 2 Medan. This study uses a qualitative method. This type of qualitative method used is naturalistic interactive, namely research on natural reciprocal relationships. Based on this qualitative approach, according to the researcher, it is very relevant because it aims to find out how the implementation of superior class program education management at MTs N 2 Medan. There are five findings in this study after data reduction/exposure is carried out, namely: the superior class program planning is the policy of the Head of the Regional Office of the Ministry of Religion. Second, organizing superior classes is carried out by establishing/holding an exceptional coordinator, a superior class program coordinator. Third, the implementation of the addition of subjects related to and the addition of tutoring. Fourth, supervision of the superior class program at MTs N 2 Medan was carried out by cooperating with the principal of the madrasah and the superior class coordinator. The last, the evaluation of the flagship class program is carried out (once a month) by tutoring in collaboration with the madrasah.